Do Competence, Information Technology, and Innovation Affect the Performance of Village-Owned Enterprises - Priharjanto, Akhmad; Andriana, Nina; Usman, Fadlil (Politeknik Ganesha Medan, 2024)
The Village-owned Enterprises’s performance that is not optimal is a question that continues to be answered. This study examines the relationship between competence, information technology and innovation on the performance of village-owned enterprises. The data used are primary data obtained through questionnaires. Questionnaires were distributed online to Directors, Secretaries, Treasurers, and Village-owned Enterprises staff in East Java from August to September 2022. The number of respondents in this study was 59 people. This research uses Structured Equation Model Partial Least Square (SEM-PLS). Data processing uses the SMART PLS4. The test was carried out in two stages, namely the measurement model test and the structural model. Data analysis was carried out by testing the measurement model and structural model. The measurement model test was carried out by testing convergent validity, discriminant validity and reliability testing. While the structural model test was carried out with the Inner Model Test consisting of R-Square, Path Coefficient, T-Statistic Test, Predictive Relevance, and Fit Model. The test results show that competence has a significant effect on innovation and performance. Meanwhile, information technology has a significant effect on innovation but does not significantly affect the Village-owned Enterprises’s performance. Simultaneous test results show that competence and technology together influence the performance through innovation.